2018
DOI: 10.5194/acp-18-16689-2018
|View full text |Cite
|
Sign up to set email alerts
|

The importance of blowing snow to halogen-containing aerosol in coastal Antarctica: influence of source region versus wind speed

Abstract: A fundamental understanding of the processes that control Antarctic aerosols is necessary in determining the aerosol impacts on climate-relevant processes from Antarctic ice cores to clouds. The first in situ observational online composition measurements by an aerosol mass spectrometer (AMS) of Antarctic aerosols were only recently performed during the Two-Season Ozone Depletion and Interaction with Aerosols Campaign (2ODIAC). 2ODIAC was deployed to sea ice on the Ross Sea near McMurdo Station over two field s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 98 publications
3
37
0
Order By: Relevance
“…Udisti et al, 2012). The results presented here suggest that, in coastal Antarctica, aerosol composition is a strong function of wind speed and that the mechanisms determining aerosol composition are likely linked to blowing snow (Giordano et al, 2018;Yang et al, 2019;Frey et al, 2020). We note that Legrand et al (2016) suggested that on average, the sea ice and open-ocean emissions equally contribute to the sea salt aerosol load of the inland Antarctic atmosphere.…”
Section: Primary Antarctic Aerosolmentioning
confidence: 58%
See 2 more Smart Citations
“…Udisti et al, 2012). The results presented here suggest that, in coastal Antarctica, aerosol composition is a strong function of wind speed and that the mechanisms determining aerosol composition are likely linked to blowing snow (Giordano et al, 2018;Yang et al, 2019;Frey et al, 2020). We note that Legrand et al (2016) suggested that on average, the sea ice and open-ocean emissions equally contribute to the sea salt aerosol load of the inland Antarctic atmosphere.…”
Section: Primary Antarctic Aerosolmentioning
confidence: 58%
“…Sea spray is almost always reported as the main source of super-micrometre (> 1 ”m) aerosols in marine areas, including the Southern Ocean and Antarctica (Quinn et al, 2015;Bertram et al, 2018). However, models of global sea salt distribution have frequently underestimated concentrations at polar locations (Gong et al, 2002). Rankin and Wolff (2003) suggested the Antarctic sea ice zone was a more important source of sea salt aerosol, during the winter months, than the open ocean.…”
Section: Primary Antarctic Aerosolmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric ambient sampling. In the clean, marine Antarctic atmosphere, the particle number concentration of primary and secondary aerosols is mainly driven by the seasonality of biological productivity in the Southern Ocean [16][17][56][57][58][59] . The mechanisms, however, for the production of either primary or secondary biogenic aerosols are not fully clarified.…”
Section: Aerosol Ambient Datamentioning
confidence: 99%
“…Peterson et al (2017) and Simpson et al 85 (2017) reported aircraft observations of the vertical distribution of BrO and aerosol extinction consistent with initial activation on snowpack followed by transport aloft (500-1000 m), where high BrO was sustained by recycling on aerosols. More recently, Frey et al (2019) and Giordano et al (2018) reported direct observations of SSA production from blowing snow above sea ice. In particular, Frey et al (2019) found that the Br − /Na + ratio of blowing snow SSA observed at 29 m above the ground decreased by a factor of 2-3 relative to observations at 2 m, suggesting rapid Br − release via (R1) from blowing snow SSA.…”
Section: Introductionmentioning
confidence: 99%